Influenza epidemiology and influenza vaccine effectiveness during the 2015-2016 season: results from the Global Influenza Hospital Surveillance Network - Puig-Barberà, Joan; Mira-Iglesias, Ainara; Burtseva, Elena; Cowling, Benjamin J; Serhat, Unal; Ruiz-Palacios, Guillermo Miguel; Launay, Odile; Kyncl, Jan; Koul, Parvaiz; Siqueira, Marilda M; Sominina, Anna; Global Influenza Hospital Surveillance Network (BMC infectious diseases, 2019)
BACKGROUND: The Global Influenza Hospital Surveillance Network is an international platform whose primary objective is to study severe cases of influenza requiring hospitalization. METHODS: During the 2015-2016 influenza season, 11 sites in the Global Influenza Hospital Surveillance Network in nine countries (Russian Federation, Czech Republic, Turkey, France, China, Spain, Mexico, India, and Brazil) participated in a prospective, active-surveillance, hospital-based epidemiological study. Influenza infection was confirmed by reverse transcription-polymerase chain reaction. Influenza vaccine effectiveness (IVE) against laboratory-confirmed influenza was estimated using a test-negative approach. RESULTS: 9882 patients with laboratory results were included of which 2415 (24.4%) were positive for influenza, including 1415 (14.3%) for A(H1N1)pdm09, 235 (2.4%) for A(H3N2), 180 (1.8%) for A not subtyped, 45 (0.5%) for B/Yamagata-lineage, 532 (5.4%) for B/Victoria-lineage, and 33 (0.3%) for B not subtyped. Of included admissions, 39% were < 5 years of age and 67% had no underlying conditions. The odds of being admitted with influenza were higher among pregnant than non-pregnant women (odds ratio, 2.82 [95% confidence interval (CI), 1.90 to 4.19]). Adjusted IVE against influenza-related hospitalization was 16.3% (95% CI, 0.4 to 29.7). Among patients targeted for influenza vaccination, adjusted IVE against hospital admission with influenza was 16.2% (95% CI, - 3.6 to 32.2) overall, 23.0% (95% CI, - 3.3 to 42.6) against A(H1N1)pdm09, and - 25.6% (95% CI, - 86.3 to 15.4) against B/Victoria lineage. CONCLUSIONS: The 2015-2016 influenza season was dominated by A(H1N1)pdm09 and B/Victoria-lineage. Hospitalization with influenza often occurred in healthy and young individuals, and pregnant women were at increased risk of influenza-related hospitalization. Influenza vaccines provided low to moderate protection against hospitalization with influenza and no protection against the predominant circulating B lineage, highlighting the need for more effective and broader influenza vaccines.
Keywords: senioři; Seasons; těhotenství; Influenza; mladiství; vakcíny proti chřipce; výsledek terapie; Influenza, Human; Middle Aged; mužské pohlaví; Epidemiological study; Prospective Studies; Adult; mladý dospělý; Influenza Vaccines; Adolescent; Influenza A Virus, H3N2 Subtype; dítě; virus chřipky A, podtyp H1N1; Child; Influenza A Virus, H1N1 Subtype; Child, Preschool; Young Adult; ženské pohlaví; Humans; předškolní dítě; prospektivní studie; Pregnancy; Vaccine; odds ratio; Virus; virus chřipky A, podtyp H3N2; lidé středního věku; Surveillance; Hospitalization; hospitalizace; dospělí; Female; Aged; roční období; chřipka lidská; Treatment Outcome; lidé; Male; Odds Ratio